2006
DOI: 10.1111/j.1365-294x.2006.02853.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in pollinator activity influence pollen dispersal and seed production of the alpine shrub Rhododendron aureum (Ericaceae)

Abstract: In alpine ecosystems, microscale variation in snowmelt timing often causes different flowering phenology of the same plant species and seasonal changes in pollinator activity. We compared the variations in insect visitation, pollen dispersal, mating patterns, and sexual reproduction of Rhododendron aureum early and late in the flowering season using five microsatellites. Insects visiting the flowers were rare early in the flowering season (mid-June), when major pollinators were bumblebee queens and flies. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 55 publications
(68 reference statements)
3
65
2
1
Order By: Relevance
“…For instance, supplemental pollinations reveal that pollinators limit fruit set in Geranium maculatum early in the season but not later; early-set fruits deplete plant resources so that late flowers are less successful [27]. Despite higher pollinator visitation rate late in the flowering season, seed set was lower owing to increased selfing in Rhodendron aureum [33]. In these latter two cases, there might be overall stabilizing selection on phenology, but it would comprise two opposing directional components.…”
Section: Interactions With Mutualists: Pollinatorsmentioning
confidence: 99%
“…For instance, supplemental pollinations reveal that pollinators limit fruit set in Geranium maculatum early in the season but not later; early-set fruits deplete plant resources so that late flowers are less successful [27]. Despite higher pollinator visitation rate late in the flowering season, seed set was lower owing to increased selfing in Rhodendron aureum [33]. In these latter two cases, there might be overall stabilizing selection on phenology, but it would comprise two opposing directional components.…”
Section: Interactions With Mutualists: Pollinatorsmentioning
confidence: 99%
“…Moreover, as members of tree species are of large plant sizes and environments are heterogeneous even within individuals' crowns, differences in outcrossing rates between upper and lower parts of their crowns have been reported (El-Kassaby et al, 1993;Patterson et al, 2004). The synchronization of flowering phenology also has a strong influence on the efficiency of pollination and, ultimately, on plants' mating systems (Hirao et al, 2006). In dichogamous species, asynchronization of flowering phenology within individual plants increases the opportunity for geitonogamous selfing.…”
Section: Introductionmentioning
confidence: 99%
“…Our study demonstrates that flowering segregation among individual plants substantially reinforces the SGS even in a continuous snow patch. Although contemporary pollen dispersal often varies depending on ecological factors such as population density (Levin and Kerster 1969), flowering phenology (Schmitt, 1983;Kitamoto et al, 2006) and seasonal changes in pollinator activity (Hirao et al, 2006), the historical gene flow across generations appears to be consistent in shaping the finescale SGS along a snowmelt gradient. Furthermore, the larger scale analyses of genetic structure in several alpine herb species (Peucedanum multivittatum, Veronica stelleri and Gentiana nipponica (Hirao and Kudo, 2004); Erythronium grandiflorum (Yamagishi et al, 2005)) revealed that the effect of snowmelt gradient on genetic structures varied among species.…”
Section: As Hirao and G Kudomentioning
confidence: 99%